If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9x + 8x + -5 + 2 + 2x = 0 Reorder the terms: -5 + 2 + -9x + 8x + 2x = 0 Combine like terms: -5 + 2 = -3 -3 + -9x + 8x + 2x = 0 Combine like terms: -9x + 8x = -1x -3 + -1x + 2x = 0 Combine like terms: -1x + 2x = 1x -3 + 1x = 0 Solving -3 + 1x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 1x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + 1x = 0 + 3 1x = 0 + 3 Combine like terms: 0 + 3 = 3 1x = 3 Divide each side by '1'. x = 3 Simplifying x = 3
| 102.5=2L+2W-11.75 | | 8t(-2t)=0 | | -4+8(4y+11)=36 | | -14x+18-11-2x+3= | | 3+2(1+5n)=65 | | 7.2(x-3.75)=-28.8 | | 6x-44*4x=22 | | 8x-2x+4=8 | | 5+2.50g=2.75 | | 12+48x+36y=528 | | 2x+2(0.25x)=5 | | 6v+3(-2v+5)=69 | | 6x-44*4x= | | 8-3x+7x-23= | | 3x+4.2=2q | | 13/4=x/12 | | 28x-35y=10 | | 52-x^2=10x | | (3/4)x-21/4 | | 2-5i/4-3i | | 38+4n=45.5+2.5n | | 7(5p-2)= | | 38*4n=45.5*2.5n | | 3(0.7z+2.8)=7(1.5z+7.2) | | x^2+2x^2=576 | | 6=4y+3 | | 5-1.6x=7.4 | | -2y-10=-2 | | 51x-y=41 | | X/51=3/17 | | 2b+5b-2=12 | | -1-3x+10x-6-1= |